Disseminating Self-Help: Positive Psychology Exercises in an Online Trial - Schueller, Stephen M; Parks, Acacia C (JMIR Publications, 2012)
BackgroundThe recent growth of positive psychology has led to a proliferation in exercises to increase positive thoughts, behaviors, and emotions. Preliminary evidence suggests that these exercises hold promise as an approach for reducing depressive symptoms. These exercises are typically researched in isolation as single exercises. The current study examined the acceptability of several multi-exercise packages using online dissemination. ObjectiveThe purpose of this study was to investigate methods of dissemination that could increase the acceptability and effectiveness of positive psychology exercises. To achieve this goal, we compared the use of positive psychology exercises when delivered in packages of 2, 4, or 6 exercises. MethodsSelf-help-seeking participants enrolled in this study by visiting an online research portal. Consenting participants were randomly assigned to receive 2, 4, or 6 positive psychology exercises (or assessments only) over a 6-week period. These exercises drew from the content of group positive psychotherapy. Participants visited an automated website that distributed exercise instructions, provided email reminders, and contained the baseline and follow-up assessments. Following each exercise, participants rated their enjoyment of the exercise, answered how often they had used each technique, and completed outcome measures. ResultsIn total, 1364 individuals consented to participate. Attrition rates across the 2-, 4-, and 6-exercise conditions were similar at 55.5% (181/326), 55.8% (203/364), and 52.7% (168/319) respectively but were significantly greater than the attrition rate of 42.5% (151/355) for the control condition (χ23 = 16.40, P < .001). Participants in the 6-exercise condition were significant more likely than participants in the 4-exercise condition to use both the third (F1,312 = 5.61, P = .02) and fourth (F1,313 = 6.03, P = .02) exercises. For 5 of the 6 exercises, enjoyment was related to continued use of the exercise at 6-week follow-up (r's = .12 to .39). All conditions produced significant reductions in depressive symptoms (F1,656 = 94.71, P < .001); however, a significant condition by time interaction (F3,656 = 4.77, P = .003) indicated that this reduction was larger in the groups that received 2 or 4 exercises compared with the 6-exercise or control condition. ConclusionIncreasing the number of exercises presented to participants increased the use of the techniques and did not increase dropout. Participants may be more likely to use these skills when presented with a variety of options. Increasing the number of exercises delivered to participants produced a curvilinear relationship with those in the 2- and 4-exercise conditions reporting larger decreases in depressive symptoms than participants in the 6-exercise or control conditions. Although research generally offers a single exercise to test isolate effects, this study supports that studying variability in dissemination can produce important findings.